Pengembangan Prototipe Detektor Kebakaran Cerdas dengan Sensor Suhu, Kelembapan, dan Api Berbasis IoT (Studi Kasus: Dinas Pendidikan Kabupaten Semarang) - Laksamana Rajendra Haidar Azani Fajri; Yusuf Wisnu Mandaya; Adhitya Purboyo; Imam Syafi'i; Ryan Yunus (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
Fire disasters can occur at any time in residential areas or schools, which are often triggered by electrical short circuits, the use of gas stoves, to minor negligence such as cigarette butts. As a preventive effort of Department of Education of Semarang, this research aims to create a prototype of a microcontroller-based early detection and fire suppression system with C programming. This tool uses NodeMCU as a control center that integrates fire sensors and DHT11 sensors to monitor room temperature in real-time. If the system detects any indication of fire or a significant temperature spike, a buzzer will activate as a warning alarm and the fan will work automatically to assist the initial extinguishing process.